Ion beam-treated space polymers: long-term stability in GEO-simulated environments - Kleiman, Jacob; Iskanderova, Zelina; Krishtein, Leonid; Dennison, J. R.; Wood, Brian; Grigorievsky, Anatoly; Best, Carl (CEAS space journal, 2021)
As part of a large program conducted between years 2010 and 2018, a number of ion beam surface treatments and proprietary coatings formed on advanced space polymers by direct ion beam deposition were developed at Integrity Testing Laboratory (ITL) Inc, in Canada. This technology allowed producing surfaces with controlled surface resistivity in a wide range of charge dissipation values, with negligibly low additional RF losses and other important functional properties, that allowed using such treated materials and products in modern space antennae, solar arrays and other external applications on spacecrafts in GEO environment. This paper will present an overview of results achieved throughout the years on enhancement of radiation stability of space polymers that were ion beam treated and coated with special multifunctional thin coatings by direct ion beam deposition. The treated/coated subjects have been ground-based tested in a range of radiation conditions, simulating the GEO radiation environment, conducted in three world-recognized GEO simulation facilities.